Radiation measurements and simulations at the PHELIX laser facility, GSI. (1st May 2022) - Behrens, R.; Hufschmidt, P.; Roth, J.; Akstaller, B.; Haag, D.; Hupe, O.; Schmidt, S.; Schreiner, S.; Michel, T.
Abstract: The absolute spectral electron and photon emission from a Tungsten target irradiated by the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility was measured inside the PHELIX target chamber. For this, a thermo-lumi-nescence detector (TLD)-based few-channel spectrometer (FCS) was used in combination with a Bayesian data analysis. The results of the FCS measurement served as input for a Monte-Carlo particle transport simulation to determine the spectra and dose out of the PHELIX target chamber. Two different simulation methods proved to be consistent and, therefore, reliable. The simulation results were compared to the dose measured with a dosemeter that consists of three Dosepix detectors in combination with a neural network analysis. The two dose results show a satisfactory agreement.